The roles of macroeconomic factors and country specific indicators in promoting international trade and FDI inflows in BRICS, ASEAN 5 and developed countries / Amirhossein Karbalaei Mohammad Hossein - Mohammad Hossein, Amirhossein Karbalaei (2015)
Total trade and foreign direct investment (FDI) are important incentives to enhance the economic development .of emerging countries. This paper aims to investigate the effects of macroeconomic and country specific indicators on total trade and FDI inflows in 16 countries, in three groups of BRICS, ASEAN 5 and developed countries for the period from 1981 to 2012. The ordinary least square and cross-sectional econometric model of fixed effect panel data are applied to explore the extent to which these variables are related in individual countries and sets of countries as a panel, respectively. In addition, the outcomes of this study help policy makers in developed and developing countries to identify influential determinants of total trade and FDI in order to optimize policies to increase international trade as well as foreign investments, and benefit from higher employment rate and economic growth. The findings from ordinary least square analysis indicate that both sets of factors are significant in influencing total trade of all countries except China where macroeconomic factors are more significant in affecting total trade. Moreover, the results from the fixed effect panel analysis also denote that both macroeconomic and country specific indicators significantly influence total trade in the three groups of countries. The findings indicate that both macroeconomic factors and country specific indicators are significant in determining FDI inflows of South Africa, Malaysia, Indonesia, the Philippines, Germany, Hong Kong, and Japan. However, it is also concluded that macroeconomic factors are more significant in affecting FDI inflows in Russia, China, Korea and the United States. Alternatively, country specific indicators are more significant in determining FDI inflows in Brazil. The findings from the fixed effect panel model indicate that FDI inflows in developed countries are significantly influenced by both sets of macroeconomic and country specific indicators. For the group of ASEAN 5 and BRICS countries, the set of macroeconomic factors are more significant in determining FDI inflows